PAPR reduction in LTE network using both peak windowing and clipping techniques - Musabe, Richard; Lionel, Mafrebo B.; Mugongo Ushindi, Victoire; Atupenda, Mugisha; Ntaganda, James; Bajpai, Gaurav (Journal of Electrical Systems and Information Technology, 2019)
Multicarrier technique orthogonal frequency division multiplexing (OFDM) modulation is a solution to provide high-speed and secured data transmission requirement in 4G technologies. Peak-to-average power ratio (PAPR) is one major drawback in OFDM system. Researches described several PAPR reduction techniques, notably peak windowing and clipping. The aim of this paper is to use these techniques to reduce PAPR. The research work describes clipping and windowing techniques such as quadratic amplitude modulation (QAM) and additive white Gaussian noise (AWGN) as channel condition. The simulation results show that in those techniques with clipping threshold level of 0.7, there is a reduction of PAPR of 8 dB, and the reduction of PAPR for the peak windowing when considering Kaiser window is about 11 dB.
Keywords: PAPR; Clipping techniques; Peak windowing; OFDM; LTE